Association between duration of phenoxybenzamine use and postoperative delirium in suspected adrenal pheochromocytoma: a retrospective cohort study - Wang, Qunying; Huang, Fusen; Wei, Ke; Wang, Jingjie; Zhu, Xin; Xiong, Qiuju; Liu, Dan (Frontiers in Medicine, 2024)
Background At present, the available evidence regarding the relationship between duration of phenoxybenzamine use and postoperative delirium is inadequate in suspected adrenal pheochromocytoma. Objective To understand how changes in the duration of phenoxybenzamine use may affect postoperative delirium. The secondary objective of this study is to explore how the duration of phenoxybenzamine use may jointly influence postoperative delirium together with other interacting variables. Methods We conducted a retrospective cohort study involving 527 participants with a preoperative diagnosis of suspected pheochromocytoma. CT characteristics, preoperative preparation, intraoperative infusion, estimated bleeding, use of intraoperative vasoactive drugs, and outcomes were obtained from all participants. Logistic regression and interaction effects were utilized to substantiate the research objectives. Results A total of 108 (20.5%) developed postoperative delirium, which was seen in 37 (18.0%) in the pheochromocytoma group and 71 (22.0%) in the non-pheochromocytoma group. The incidence of postoperative delirium showed no statistically significant differences in the two groups. A positive association between the duration of phenoxybenzamine use and the risk of postoperative delirium was observed (OR = 1.05, 95%CI = 1.03–1.08, p < 0.01), independent of confounders. The relationship between the duration of phenoxybenzamine use and postoperative delirium differed according to the presence or absence of pheochromocytoma, suggesting an interactive effect (p < 0.05). Conclusion This study highlights the influence of inappropriate duration of phenoxybenzamine use on the risk of incident postoperative delirium, independent of confounders. The effect of duration of phenoxybenzamine use causes a further increase in the risk of postoperative delirium, especially in non-pheochromocytomas.